2023
DOI: 10.3233/bmr-210377
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of different surgical methods in the treatment of acute central cord syndrome without fractures and dislocations of the cervical spine

Abstract: BACKGROUND: Acute central cord syndrome (ACCS) without fractures or dislocations is the most common form of incomplete spinal cord injury. OBJECTIVE: To evaluate the effectiveness of different surgical methods in the treatment of acute central cord syndrome without fractures or dislocations of the cervical spine. METHODS: A total of 164 patients with ACCS without fracture or dislocation of the cervical spine treated in our hospital from May 2018 to October 2019 were recruited and assigned to study group A and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Similarly, laminoplasty and laminectomy appear equivalent as far as neurological outcome is concerned (17). In the study of Jia et al comparing 164 patients with acute central cord syndrome who underwent either the anterior cervical discectomy or posterior cervical laminectomy, the authors found similar results between the two approaches, with a slight superiority of the laminectomy technique (6). A more recent retrospective study by Yang et al regarding the management of patients with SCI also suggests that traumatic edema of the spinal cord is better resolved when an early laminoplasty is performed (20).…”
Section: Laminectomy-laminoplastymentioning
confidence: 98%
See 2 more Smart Citations
“…Similarly, laminoplasty and laminectomy appear equivalent as far as neurological outcome is concerned (17). In the study of Jia et al comparing 164 patients with acute central cord syndrome who underwent either the anterior cervical discectomy or posterior cervical laminectomy, the authors found similar results between the two approaches, with a slight superiority of the laminectomy technique (6). A more recent retrospective study by Yang et al regarding the management of patients with SCI also suggests that traumatic edema of the spinal cord is better resolved when an early laminoplasty is performed (20).…”
Section: Laminectomy-laminoplastymentioning
confidence: 98%
“…Central cord syndrome (CCS) is the most common type of incomplete spinal cord injury. The common setting of CCS without apparent osteoligamentous injury appears to be the closest analog of SCI without compromise of the spinal canal in adults ( 6 ). After the primary insult, a plethora of secondary events occur, with progressive edema and hemorrhage predominating and possibly being the cause of spinal cord compression ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, posterior approaches are commonly regarded as more favorable for managing multi-segmental cervical canal stenosis due to their reduced incidence of complications, this may be attributed to factors such as reduced manipulation of vital structures like blood vessels and esophagus during surgery. Minimizing these risks can play a role in enhancing patient results and expediting the recovery process [11] . The techniques of laminectomy fusion xation and single open-door laminoplasty are widely employed among the posterior surgical options for cases of CCSWOFD.…”
Section: Introductionmentioning
confidence: 99%
“…However, for patients with SLIC score ≥ 4, there are few studies on whether the surgical approach should be anterior-posterior or anterior-posterior. Whether the quantitative score of SLIC for patients with lower cervical injury before surgery can be used as a guideline for clinical selection of surgical approaches remains to be clinically verified [4]. Based on this, this research group took 75 patients with lower cervical spine injury admitted to the First Affiliated Hospital of Hebei North University from January 2020 to November 2022 as the research object, and obtained evidence-based evidence by analyzing the correlation between preoperative SLIC score and surgical approach as well as postoperative efficacy, which provided scientific reference for the selection of surgical approach for cervical spine injury under correct clinical guidance.…”
Section: Introductionmentioning
confidence: 99%